Purification and structural elucidation of chondroitin sulfate/dermatan sulfate from Atlantic bluefin tuna (Thunnus thynnus) skins and their anticoagulant and ACE inhibitory activities. Issue 66 (12th November 2018) - Krichen, Fatma; Bougatef, Hajer; Capitani, Federica; Ben Amor, Ikram; Koubaa, Imed; Gargouri, Jalel; Maccari, Francesca; Mantovani, Veronica; Galeotti, Fabio; Volpi, Nicola; Bougatef, Ali
Abstract : Chondroitin sulfate/dermatan sulfate (CS/DS) was extracted from Atlantic bluefin tuna ( Thunnus thynnus ) skin (SGAT) and was purified and characterized. Abstract : Chondroitin sulfate/dermatan sulfate (CS/DS) was extracted from Atlantic bluefin tuna ( Thunnus thynnus ) skin (SGAT) and was purified and characterized. SGAT was characterized by acetate cellulose electrophoresis, FTIR spectroscopy, 13 C NMR spectroscopy and SAX-HPLC. According to the results obtained for specific chondroitinases (ABC and AC) and the SAX-HPLC separation of generated unsaturated repeating disaccharides, the polymer was found to contain a disaccharide monosulfated in positions 6 and 4 of GalNAc and disulfated disaccharides in different percentages. These results were confirmed by 13 C NMR experiments. The average molecular mass was 24.07 kDa, as determined by PAGE analysis. SGAT was evaluated for its in vitro anticoagulant activity via activated partial thromboplastin time, thrombin time and prothrombin time tests. The polymer showed strong inhibitory activity against angiotensin I-converting enzyme (IC50 = 0.25 mg mL −1 ). Overall, the results suggest that this newly extracted CS/DS can be useful for pharmacological applications.